Pengaruh Kualitas Pelayanan, Fasilitas dan Lokasi Terhadap Kepuasan Pasien Pada Rumah Sakit XY - Putri, Wahyu Thahara Kusumaning; Surianto, Moh. Agung (Jurnal EMT KITA, 2024)
The purpose of this research was to determine and analyze the influence of service quality, facilities, and location on patient satisfaction at XY Hospital. In this research, the sample size was taken using the Slovin formula, totaling 338 respondens. The sampling technique used nonprobability sampling. Data was taken using a questionnaire which was measured using a Likert scale. This research uses multiple linear regression analysis with the help of SPSS version 25 software. The results of this research show that Facilities have a partial influence on Patient Satisfaction, but Service Quality and Location do not have a partial influence on Patient Satisfaction. The results of this research also show that Service Quality, Facilities and Location simultaneously influence Patient Satisfaction.